PRAPERADILAN TERHADAP SURAT PERINTAH PENGHENTIAN PENYIDIKAN (SP3) OLEH KEPOLISIAN (Analisis Putusan Pengadilan Negeri Nomor 02/Pid.Prap/2020/PN.Ttd) - Fauziah, Fauziah; Putra Sitorus, Andi (Jurnal Perspektif Hukum, 2024)
This pretrial is regulated in Article 77 of the Criminal Procedure Code, which contains the district court is authorized to examine and decide, in accordance with the provisions stipulated in the law. This writing uses a library research method to examine secondary data and the type of data in this research is secondary data. Primary and secondary legal materials are arranged systematically and analyzed qualitatively. The results of the research show that the legal arrangements governing pretrial in the legal process of criminal cases are regulated in Article 77 to Article 83 of the Criminal Procedure Code and after the issuance of the Constitutional Court Decision Number 21/PUU-XII/2014 added the determination of suspects, searches, and seizures included as pretrial objects. The judge's consideration in examining and deciding the pretrial case of the termination of investigation by the police in the case of embezzlement in office was to grant the pretrial application because the termination of investigation of the criminal case of embezzlement in office had been carried out by the first respondent and second respondent unprocedurally by not carrying out the provisions that had been expressly regulated both in Article 109 paragraphs (1) and (3) of the Criminal Procedure Code and in Article 15 of the National Police Chief Regulation Number 14 of 2012.